2007
DOI: 10.1002/jbm.a.31244
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of nickel from 316L stainless steel into contacting osteoblastic cells and metal ion interference with BMP‐2‐induced alkaline phosphatase

Abstract: Bone cells contacting nickel (Ni)-containing implant materials may be affected by Ni species via disturbed signaling pathways involved in bone cell development. Here we analyze effects of the Ni-containing steel 316L and major metal constituents thereof on bone morphogenetic protein-2 (BMP-2)-induced alkaline phosphatase (ALP) of MC3T3-E1 cells. While cells grew normally on 316L, cellular Ni content increased 10-fold vs. control within 4 days. With respect to the major components of 316L, Ni2+ (3-50 microM) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…BMP‐2 is an important molecule involved in bone formation, which induces transcription factors such as Runx2. The BMP signaling pathway also plays a role in osteoblast differentiation, as well as the synthesis and secretion of the extracellular matrix (Meng et al, ; Molders, Felix, Bingmann, Hirner, & Wiemann, ). In our present study, at both gene and protein levels, we discovered that MGO nanoparticles could promote BMP‐2 expression, which in turn accelerated Runx2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…BMP‐2 is an important molecule involved in bone formation, which induces transcription factors such as Runx2. The BMP signaling pathway also plays a role in osteoblast differentiation, as well as the synthesis and secretion of the extracellular matrix (Meng et al, ; Molders, Felix, Bingmann, Hirner, & Wiemann, ). In our present study, at both gene and protein levels, we discovered that MGO nanoparticles could promote BMP‐2 expression, which in turn accelerated Runx2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Co(II) can significantly reduce the movement ability of macrophages and inhibit cell migration by RhoA downregulation and cytoskeleton reorganization, which is still happened by the emergence of ROS [57]. Ni ions gradually accumulated in cells also affect the ability of bone morphogenetic protein (BMP-2) to induce alkaline phosphatase (ALP) formation [58,59]. Some studies have shown that compared with Nitinol, the surface layer rich in Ti or Ta can significantly reduce the formation of ROS and longevity protein free radicals [60].…”
Section: Different Metal Ions Can Induce Cell Damagementioning
confidence: 99%
“…It is not clear the molecular mechanism of BMP-1 differentially expressed in BMSCs grown on Bio-Oss ® and R.T.R ® . It is possible that the difference of BMP-1 expression level caused by the difference of zinc ion content in the two materials may lead to the obvious difference of BMSCs differentiating into osteoblasts 32) .…”
Section: Discussionmentioning
confidence: 99%